O ajuste fiscal de médio prazo: o que vai acontecer quando as receitas extraordinárias acabarem? (Economia Aplicada, 2000)
This paper discusses the prospects for the medium term fiscal adjustment in Brazil, based on the literature about the sustainability of fiscal policy. It shows that, from 2002 onwards, when the government will no more colect the windfall revenues from the CPMF and the concessions of public services, the primary surplus could fall significantly if compared with the surplus expected for the period 1999/2001. Exercises involving the dynamics of the public spending, based on the building of medium term scenarios for the public finances, motivate the proposal of reducing gradually the windfall revenues, instead of eliminating them abruptly in June 2002.